RESEARCH ON THE POINT SERVICE EFFICIENCY IN A FEMININE VOLLEYBALL TEAM (PENICILINA IAŞI, A1 DIVISION, 2009-2010 SEASON) - Rareș PUNI; Cătălin ȘTIRBU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2011)
Service is considered to be one of the essential technical elements in volleyball, "a fix moment" where the ballis sent back in the game. Its execution is exclusively determined by the player's individual qualities, not by the actionsof the co-players or those of the opponents. This is why special attention is given to service quality during trainingsessions.Our study aims at analyzing, by the means of the statistical analysis, the efficiency of the point services withinPenicilina Ia